Animism is Applied Ethnobotany: A Shamanic Healing Ritual with the Dayak Benuaq Ohookng / East Kalimantan - Herwig Zahorka (Journal of Tropical Ethnobiology, 2020)
The Dayak Benuaq Ohookng people believe in many and diverse territorial ghosts/spirits (wook) who exist in the environment, some of which have the power to remove the soul (juus) of a human body part or organ and, at the same time, implant disease. Consequently, this body part or organ gets sick. The mission of the shamans (pembeliatn), as mediums to the spiritual world, is to identify the ghost/spirit responsible during nocturnal rituals and to submit all of the diverse ritual offerings possible, including making an exchange of a “soul” (kelakar) made from ironwood (Eusideroxylon zwageri). To get rid of the disease, the patient smears some of his/her own saliva onto a carved statue (sepatukng silih), depicting the ghost/spirit concerned, after the shaman activated it. Later, this statue is taken to the forest. The shaman can also extract the disease from the sick body part by help of a thinly spliced banana leaf (telolo). The disease can also be attached to the statue or put into the blood of sacrificial animals. In order to finally find and identify the lost soul of the patient’s sick body part, the shaman performs a vigorous dance and then falls into a trance, during which he receives a message about where to catch the soul. To discover the soul and capture it, he uses a bamboo stick filled with boiled rice (tolakng tintikng). The captured soul is then massaged into the sick body part of the patient. To perform this ritual, a great number of traditional and institutionalized plants are essential. They are arranged around the altar (balai sianca jadi) and used for ritual objects. White rice and rice colored with black, red, yellow and green dyes plays an important role in attracting and satisfying the ghosts.